The SPARC-related modular calcium binding protein 2 ( SMOC2 ) gene polymorphism in primary glaucoma: a case-control study - Al-Dabbagh, Najwa; Al-Shahrani, Hamoud; Al-Dohayan, Nourah; Mustafa, Md; Arfin, Misbahul; Al-Asmari, Abdulrahman (Clinical ophthalmology (Auckland, N.Z.), 2017)
Primary glaucomas are among the most common eye diseases that may potentially result in bilateral blindness. Both genetics and environmental factors are reported to be involved in the etiology of primary glaucomas. Secreted protein acidic and rich in cysteine (SPARC)-related modular calcium binding protein 2 (SMOC2) is a matricellular glycoprotein encoded by the gene and known to regulate the expression of extracellular matrix (ECM) proteins and matrix metalloproteinases (MMPs), which play an important role in the pathogenesis of primary glaucomas. The frequencies of alleles and genotypes of variants were examined in 406 Saudi subjects, including primary open angle glaucoma (POAG, n=140) and primary angle closure glaucoma (PACG, n=64) patients and 202 matched healthy controls using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Genotyping of polymorphism (rs13208776) revealed a significantly higher frequency of the heterozygous genotype GA ( <0.01) and a lower frequency of wild type GG genotype ( =0.05) in glaucoma patients compared to the controls. Upon stratification of the patients on the basis of types of glaucoma, PACG patients had a significantly higher frequency of GA genotype as compared to the controls ( <0.01), whereas there was no significant difference between the POAG patient and control groups in frequencies of alleles and genotypes. Further, there was no significant difference in frequency distribution of alleles and genotypes between male and female patients. This study indicates that the GA genotype of (G>A) polymorphism is significantly associated with PACG and may be a risk factor. However, further large-scale studies in the Saudi population as well as in other ethnic populations are needed to confirm this association.